Sosialisasi dan Pelatihan Penggunaan Aplikasi CBT E-Ujian dalam Meningkatkan Literasi Digital Guru di SMK Negeri 3 Jayapura - Riswan, Muh.; Akbar, Sahrul; Mutiara Sogalrey, Febi Adriana; Bubui, Erastus Balvin (Universitas Andi Djemma, 2025)
The integration of digital technology into the education system requires teachers to have adequate digital literacy, particularly in managing technology-based learning evaluations. At SMK Negeri 3 Jayapura, most teachers are unfamiliar with using the Computer-Based Test (CBT) application (E-Ujian) due to a lack of training and limited infrastructure. This community service activity aims to improve teachers' digital competence through socialization and training on the use of the CBT application (E-Ujian). The method used was classical, hands-on training, implemented in three stages: preparation, implementation, and evaluation. A total of 17 teachers participated in this activity, which was evaluated through pre- and post-tests. The results showed a significant increase in mastery, from 64.7% of participants before the training at a mastery level below 50%, which decreased to 11.7% after the training. Furthermore, 89% of participants expressed very high satisfaction with the implementation of the activity. These results indicate that systematic, hands-on training can improve teachers' digital literacy in designing, managing, and evaluating computer-based exams.